Subjective Financial Knowledge dan Financial Well-Being: Peran Financial Behavior - Desta Rizky Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the relationship between subjective financial knowledge and financial well-being with financial behavior as a mediator. This study uses a quantitative approach with an explanatory method. Data was collected through a questionnaire with a sample of generation Z in Yogyakarta using purposive sampling techniques. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) through Smart PLS 4.0 software. The results show that subjective financial knowledge does not affect financial well-being. However, the role of financial behavior as a mediator in this study indicates a positive relationship between subjective financial knowledge on financial well-being.